Noncanonical WNT5A controls the activation of latent TGF-β to drive fibroblast activation and tissue fibrosis - Trinh-Minh, Thuong; Chen, Chih-Wei; Tran-Manh, Cuong; Li, Yi Nan; Zhu, Honglin; Zhou, Xiang; Chakraborty, Debomita; Zhang, Yun; Rauber, Simon; Dees, Clara; Lin, Neng-Yu; Kah, Delf-Thorge Eric; et al. (Journal of Clinical Investigation, 2024)
Transforming growth factor β (TGF-β) signaling is a core pathway of fibrosis, but the molecular regulation of the activation of latent TGF-β remains incompletely understood. Here, we demonstrate a crucial role of WNT5A/JNK/ROCK signaling that rapidly coordinates the activation of latent TGF-β in fibrotic diseases. WNT5A was identified as a predominant noncanonical WNT ligand in fibrotic diseases such as systemic sclerosis, sclerodermatous chronic graft-versus-host disease, and idiopathic pulmonary fibrosis, stimulating fibroblast-to-myofibroblast transition and tissue fibrosis by activation of latent TGF-β. The activation of latent TGF-β requires rapid JNK- and ROCK-dependent cytoskeletal rearrangements and integrin αV (ITGAV). Conditional ablation of WNT5A or its downstream targets prevented activation of latent TGF-β, rebalanced TGF-β signaling, and ameliorated experimental fibrosis. We thus uncovered what we believe to be a novel mechanism for the aberrant activation of latent TGF-β in fibrotic diseases and provided evidence for targeting WNT5A/JNK/ROCK signaling in fibrotic diseases as a new therapeutic approach.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Dermatology; Fibrosis; Pulmonology